The Nipas Law and the Management of Protected Areas in the Philippines - Custodio, Carlo C.; Molinyawe, Norma M. (Silliman Journal, 2022)
The passage of the Republic Act 7586 otherwise known as NIPAS Act during the Fifth Regular Session of Congress on the 22"' of July 1991 represented a significant move towards the management of pro-tected areas in the country. Its Implementing Rules and Regulations were issued as DENR Administrative Order No. 25 (DAG 25) on 29111 June 1992. At the heart of the Nipas Act is the Declaration of Policy which underscores, among other things, "the critical importance of proteaing and maintaining the natural biological and physical diversities of the environment, notably on areas with unique features to curtain human lift and development, as well as plant and animal life." In view of the magnitude of this task, no less than the powers of the State are invoked in order to secure for the present andfuture generations qf Filipinos "the perpetual existence of all native plants and animals." in this end, a comprehensive system of integrated protected areas within the classification of national park as provided for by the Constitution has been estab-lished, and henceforth known as the National integrated Protected Ar-eas System or NIPAS. Its grand objectives notwithstanding, the actual implementation of NIPAS Law remains fraught with controversy and, in many cases, both its substance and implementation continue to be mired in conflict. This paper critically reviews the salient points of NIPA S, examines some of the inherent weaknesses in its provisions, and analyzes the problem areas that impede the effective compliance of its requirements the whole, undermine the very intent of its establishment. In turn, this paper offers important suggestions, foremost of which is the call for a major change in attitude within the ranks of the DENR staff and the other program implementors. Specifically, this change of attitude involves no less than a call for DENR personnel "to cease being known as erilrirc-ers of regulations, but to consider themselves as development workers Finalily, in judging results, the paper underscores the need for implemen-tors to go beyond the step-by-step compliance of requirements and to pay equally careful attention to the achievement of objectives, while high-lighting the importance of a truly participative and constiliative process of managing the natural resources of this country.